Tissue Thickness Interferes With the Estimation of the Immunohistochemical Intensity: Introduction of a Control System for Managing Tissue Thickness. Issue 2 (February 2021) - Masuda, Shinobu; Suzuki, Ryohei; Kitano, Yuriko; Nishimaki, Haruna; Kobayashi, Hiroko; Nakanishi, Yoko; Yokoi, Hideo
Abstract : Context and Objective: The conversion of immunohistochemical (IHC) results from 3-dimensional tissue to a 2-dimensional visual image without considering tissue thickness poses a considerable risk of misleading IHC intensities. The present study aimed to clarify whether tissue thickness interferes with the estimation of IHC staining intensity and to introduce a control system to manage it. Design: We prepared cell lines that are used as controls for human epidermal growth factor receptor 2 (HER2) IHC (MDA-MB-231, MDA-MB-175VII, MDA-MV-453, and SK-BR-3), a polyclonal antibody for HER2, an interferometry to measure the tissue thickness of formalin-fixed paraffin-embedded sections, a microscope with a Halogen or an LED light source, a complementary metal-oxide semiconductor camera in which the output signal can be corrected to γ=1, and a program to estimate color elements (hue, saturation, and luminance). It was examined whether tissue thickness interferes with the experimental scoring systems and practical classification of the routine HER2 scoring system. Results: A noncellular control was shown to be better than a cellular control for managing tissue thickness. The IHC intensity for HER2 was correlated with tissue thickness ( R 2 =0.8094), even under the less-standardized condition, but this correlation was better under the improved standardized condition using corrected γ=1 ( R 2 =0.9282). Discrepancies in practical HER2 scores were increased in sections with thicknesses <2 and >5 μm. A control system to manage tissue thickness was introduced. Conclusions: Tissue thickness interferes with the estimation of the IHC intensity of HER2 in both experimental and practical scoring systems. A control system for managing tissue thickness is essential to increase the benefits of IHC as a standardized assay for clinical applications. Abstract : Supplemental Digital Content is available in the text.